The Effect of Smoking on Carbon Monoxide Respiration among Active Smokers in Palembang City, Indonesia - Sitorus, Rico Januar; Purba, Imelda Gernauli; Natalia, Merry; Tantrakarnapa, Kraichat (Kesmas, 2021)
Smoking leads to disease and disability as well as harm nearly every organ of the body. Furthermore, smoking of tobacco is known to cause pulmonary dysfunction and lead to complications, pain, or even death. This study aimed to measure the risk factors for the respiration of carbon monoxide among smokers. A cross-sectional design was implemented by involving 156 smokers in Karyajaya Subdistrict, Palembang City. The dependent variable was carbon monoxide levels (ppm), while the independent variables were smoking frequency, duration, and the last period of smoking. The carbon monoxide levels (ppm) measured with a PiCO + Smokerlyzer® device from Bedfont Scientific Limited were the research tool and the independent variables of the questionnaire. The Pearson Correlation and multiple linear regression were used for the analysis. The results of the multiple linear regression analysis revealed that smoking duration assessment is related to carbon monoxide respiration after controlling smoking frequency, the last period of smoking, and the distance of residence to sources of exposure. The smoker's respiration of carbon monoxide level was 72.5% influenced by the duration, frequency, last period of smoking, and distance of residence to sources of exposure. Reducing the frequency of smoking and stopping may prevent and control carbon monoxide respiration.